2016
DOI: 10.1002/14651858.cd012224
|View full text |Cite
|
Sign up to set email alerts
|

Manual therapy and exercise for rotator cuff disease

Abstract: Despite identifying 60 eligible trials, only one trial compared a combination of manual therapy and exercise reflective of common current practice to placebo. We judged it to be of high quality and found no clinically important differences between groups in any outcome. Effects of manual therapy and exercise may be similar to those of glucocorticoid injection and arthroscopic subacromial decompression, but this is based on low quality evidence. Adverse events associated with manual therapy and exercise are rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
149
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(169 citation statements)
references
References 157 publications
(2 reference statements)
6
149
0
1
Order By: Relevance
“…We do not know how many patients attend physiotherapy following informal referral or recommendation from their GP. Further, uncertainty regarding the efficacy of exercise (recent Cochrane review published after the National survey) [49] may also impact on GPs decision making when managing RCRP. Finally, Australia has a maldistributed GP workforce [50] and a rapidly increasing population attendance rate to general practice [51], so it is possible that GPs lack the time to adequately assess and manage RCRP within their primary care setting [31,47].…”
Section: Gp Management Of Rcrpmentioning
confidence: 99%
“…We do not know how many patients attend physiotherapy following informal referral or recommendation from their GP. Further, uncertainty regarding the efficacy of exercise (recent Cochrane review published after the National survey) [49] may also impact on GPs decision making when managing RCRP. Finally, Australia has a maldistributed GP workforce [50] and a rapidly increasing population attendance rate to general practice [51], so it is possible that GPs lack the time to adequately assess and manage RCRP within their primary care setting [31,47].…”
Section: Gp Management Of Rcrpmentioning
confidence: 99%
“…The MT and exercise are common treatment methods for SIS as a part of physical therapy. Improving function and ROM and decreasing pain are the main goals of both treatments [18,19]. A recently published metaanalysis reported that corticosteroids were superior to control and physical therapy modalities, but only during a short-term follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…glucocorticoid injection) [2]. Studies that consider physiotherapy for treating shoulder pain and function showed that active physiotherapy has a significant benefit to the patients in short-and longterm compared to non-or placebo-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therapies to treat musculoskeletal disorders of the shoulder are amongst others the manual therapy, the therapeutic ultrasound, low-level laser therapy, acupuncture and the pulsed or static electromagnetic field therapy, applied alone or in combination [2]. Kuhn summarized the outcome of eleven randomized, controlled trials to demonstrate that exercise (as applied in rehabilitation programs) in the treatment of rotator cuff impingement has statistically and clinically benefits on pain reduction and improvement of function [3].…”
Section: Methodsmentioning
confidence: 99%